TURIZM SOHASIDAGI TADQIQOTLARNING LEKSIKOGRAFIK XILMA-XILLIGI XUSUSIDA - Raximova Gulsanam (International Scientific and Current Research Conferences, 2023)
This article provides a scientific justification for the fact that the definition explaining the interpretation of the word-term and the peculiarities of its use has a priority element of the tourist vocabulary, for example, in explanatory, historical and etymological dictionaries, many terms are given in the form of words with a general literary meaning and in most cases are not distinguished as a special dictionary. In particular, scientists in this field E.A. Shilova, O.A. Uzhova, S.X. Analyzes the scientific research of Argashokova and others. about the variety of tourist units that exist today.